The Amharic Definite Marker and the Syntax-Morphology Interface - Kramer, Ruth (Syntax (Oxford, England), 2010)
.  The definite marker in Amharic has an unusually complex pattern of distribution—its position varies depending on whether the DP contains an adjective, a relative clause, multiple adjuncts, a demonstrative, or just a noun. In this paper, a minimalist/Distributed Morphology analysis of the definite marker is developed based on the idea that the definite marker is the realization of D when it is obligatory, and the reflex of a definiteness agreement process when it is optional. Evidence is presented that D undergoes the morphological operation Local Dislocation (Embick & Noyer 2001) in Amharic, and that Local Dislocation is subject to the Phase Impenetrability Condition—the definite marker cannot attach within a phase that has been previously spelled out. Definiteness agreement, however, does not seem to respect phase impenetrability, which leads to the suggestion that phase impenetrability is only relevant after Linearization. From a broader perspective, the paper explores the effect of minimalist assumptions about syntactic cyclicity (cyclic spell‐out by phase, phase impenetrability) on the cyclicity of morphological operations.